The Parliamentary guide and work of general reference 1898-9 [electronic resource] : for Canada, the provinces, Northwest Territories and Newfoundland : containing election returns, lists and sketches of members, cabinets of the U.K., U.S. and Canada, customs and excise tariffs, constitution of Canada and governments and legislatures of all the provinces, electoral population and census returns, new Franchise Act, plebiscite returns, proceedings of colonial conferences, militia staff, etc. - Magurn, Arnott J. (Arnott James) (Winnipeg : Manitoba Free Press; Ottawa : J. Hope, 1898)
Tables. Includes biographies and list of members for all the provincial legislatures. Includes advertising matter. Duplicate of CIHM microfiche no. 32050. Electronic reproduction. Mode of access: Internet. 44